College Assistance in Improving Reading and Understanding Skills of the Qur'an in Pantai Gemi Village - Ningratri, Yuni Asri; Khairunnisa, Anita; Hanum, Atiqoh (Jurnal Riset Ilmu Pendidikan, 2024)
Higher education as a forum for the community to obtain an improvement in the welfare of living standards through science and knowledge. The presence and role of universities is very large in the midst of people's lives in order to educate and advance the life of the nation by practicing science. Gemi Beach is one of the villages in Stabat District, Lalat Regency, North Sumatra Province. With a population of around 9,021 people and around 92.78% of the people of Pantai Gemi Village are Muslims. With the existence of the majority Muslim community in Pantai Gemi Village, Stabat District, Langkat Regency, the community service team of the Tarbiyah Science College (STITAW) Binjai City provides several community service activity programs in the form of learning activities in the form of the ability to read and understand the Qur'an to the people of Pantai Gemi Village. This service activity lasted for 1 month. Community service activities are carried out with a Community Development approach, which is an approach oriented to efforts in developing Islamic education in the village by making the community the subject and object of development. Guidance on reading the Qur'an is carried out with a method that focuses on important aspects for Tajweed, such as correct pronunciation, makharijul letters, and the rules of tajweed, which are very important for accurate reading of the Qur'an. Reading and understanding the Qur'an must also be done interactively. Through the implementation of community service activities related to tutoring reading and learning and understanding the Qur'an, it has succeeded in improving the reading and understanding of the Qur'an for children in Pantai Gemi Village, Stabat District, Langkat Regency. This activity aims to enable children to read the Qur'an properly and in accordance with tajweed and practice knowledge that is useful to the Qur'an, as well as the community in Pantai Gemi Village can produce children who excel in the religious field and have spiritual intelligence.